Parent-teacher involvement in career guidance program for a minority group - Osdeg, Corazon T. (Animo Repository, 1976)
This study aims to propose a functional parent-teacher involvement in the guidance program of the school and in the career decision-making process of the high school students. The descriptive method of research was used in this study. A survey was conducted on 200 students, 120 parents, and 7 faculty members of Kalinga Academy in the school year 1975-1976. An interview with the school principal was also conducted. Three questionnaires were distributed separately to the students, teachers, and parents to survey the need for a guidance program. The results of the study revealed that the problem areas of the students of Kalinga Academy were the following : future vocational educational problems finances living conditions and employment health physical development social and recreational problems home and family problems curriculum and teaching problems personal psychological problems courtship, sex, and marriage morals and religious problems and social psychological problems. It was also found that the parents and teachers of Kalinga Academy needed guidance information and knowledge through an in-service training program. Also, the career preferences of the students of Kalinga Academy were those which led towards white-collared jobs. The parents usually decided for their children because of the strong cultural practices and traditions and their career choices for their children were strongly motivated by factors like prestige, social admiration and status. It was further concluded that the program of services that would best satisfy the needs of the students and effect changes in the school were individual inventory, information, counseling, testing, placement, follow-up services, and parent-teacher involvement in guidance.